Pressures on Journalists in the Digital Age: A Systematic Review - Surokim Surokim; Rachmah Ida (Universitas Bhayangkara Surabaya, 2026)
Journalistic operating conditions have profoundly transformed in the digital era. Beyond established political and institutional pressures, journalists contend with new constraints from digital platforms, online harassment, and media economic restructuring, raising critical concerns for press freedom, autonomy, and sustainable news production. While scholarly focus on these pressures has grown, the literature remains fragmented across disciplines, geographies, and themes. This study synthesizes research on journalistic pressures via a systematic literature review of Scopus-indexed, peer-reviewed publications. Adhering to PRISMA 2020 guidelines, the review analyzes 637 articles (1984-2024), examining temporal trends, research production patterns, disciplinary distributions, and thematic evolution. Findings show rapid scholarship growth in the last decade, mirroring intensified concerns over digital hostility, platform visibility, and economic shifts. Research production is concentrated in Global North institutions, indicating persistent imbalances. Five dominant themes emerge: political/institutional pressures, digital harassment/networked hostility, organizational/economic constraints, journalists' psychological impacts, and digital platforms' influence. By mapping four decades of scholarship, this study offers an integrated perspective on pressures in digitally mediated societies, identifying crucial avenues for future research in journalism and communication studies.